2015
DOI: 10.4236/pp.2015.62009
|View full text |Cite
|
Sign up to set email alerts
|

The Adverse Event Profile in Patients Treated with Transferon<sup>TM</sup> (Dialyzable Leukocyte Extracts): A Preliminary Report

Abstract: Background: Dialyzable leukocyte extracts (DLE) are heterogeneous mixtures of peptides less than 10 kDa in size that are used as immunomodulatory adjuvants in immune-mediated diseases. Transferon TM is DLE manufactured by National Polytechnic Institute (IPN), and is registered by Mexican health-regulatory authorities as an immunomodulatory drug and commercialized nationally. The proposed mechanism of action of Transferon TM is induction of a Th1 immunoregulatory response. Despite that it is widely used, to dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 23 publications
1
5
0
2
Order By: Relevance
“…It is produced under Good Manufactoring Practice processes and facilities. Serious adverse events had not been reported and a recent safety assessment has confirmed that adverse events associated with Transferon™ are rare and nonserious [30]. Transferon™ has been approved by the Mexican drug regulatory agency (COFEPRIS) for human consumption as an immunomodulatory agent, and a robust biological assay has been developed to serve as a quality control, ensuring an adequate and measurable activity of Transferon™ [31].…”
Section: Introductionmentioning
confidence: 99%
“…It is produced under Good Manufactoring Practice processes and facilities. Serious adverse events had not been reported and a recent safety assessment has confirmed that adverse events associated with Transferon™ are rare and nonserious [30]. Transferon™ has been approved by the Mexican drug regulatory agency (COFEPRIS) for human consumption as an immunomodulatory agent, and a robust biological assay has been developed to serve as a quality control, ensuring an adequate and measurable activity of Transferon™ [31].…”
Section: Introductionmentioning
confidence: 99%
“…En 63 %, los EA se presentaron entre los días 1 y 4 del tratamiento y el tiempo de resolución fue de 14 días. 18 En el caso que describimos, y basados en la temporalidad, el posible EA fue la reactivación de las lesiones de MF, que se presentó antes de 48 horas del inicio del EDLH, y al igual que en el estudio mencionado, las lesiones remitieron antes de dos semanas al suspender el extracto.…”
Section: Discussionunclassified
“…“Transferon Oral” has been used as an auxiliary treatment in patients with inflammatory diseases ( Hernandez et al, 2013 ; Homber et al, 2015 ). “Transferon Oral” improves resolution of infectious diseases by increasing the number of systemic IFN-γ cells in ocular fungal keratitis and enhances the survival of pediatric patients with sepsis by lowering C reactive protein (CRP), rising increases total lymphocyte numbers and decreasing total neutrophil count ( Santacruz-Valdes et al, 2010 ; Castrejon Vazquez et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%